Long Term Impact Profitability of Market Share Islamic Bank in Indonesia - Chitra Yuliashri Katili; Rifadli D Kadir (UIN Siber Syekh Nurjati Cirebon, 2023)
This paper aims to analyze the influence of the internal variables of Islamic banks on market share. Market share is one of the indicators used by Islamic banking to measure how much it contributes to the banking industry in Indonesia. The internal variables of Islamic banks used are Return On Assets, Capital Adequacy Ratio, Financing to Deposit Ratio, and Non Performing Financing. The relationship between bank internal variables and market share is measured using long-term regression, namely fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) regressions. Based on the results of this regression, it shows that the profitability variable proxied by Return On Assets and the Financing to deposit Ratio variable has a positive effect on the market share of Islamic banks in Indonesia. The Capital Adequacy Ratio and Non-Performing Financing variables reject the proposed hypothesis. These results conclude that in the long-term the market share of the variable return on assets and the financing to deposit ratio can increase the market share of Islamic banking in Indonesia.